THE EFFECT OF BRAINSTORMING TECHNIQUE IN PROMOTING STUDENTS' SPEAKING SKILL AT UPT SMPN 4 PINRANG - Dwi Handayani Lukman; Nurdevi Bte Abdul; Sujariati (FKIP Unismuh Makassar, 2022)
This research aimed to know the effect of brainstorming technique in fluency and accuracy of the students’ speaking skill. The population for research was the eighth grade (VIII.6) of UPT SMPN 4 Pinrang that consist of 32 student. This research used quantitative method, with pre-experimental research. The instrument that used to collecting the data was test for students speaking in descriptive text.For results of the information; it appears that the understudies cruel score of pre-test in familiarity is 63.59. While the post-test is higher than mean score of pre-test, it is 80.31. With this improvement, it means that there is a significant difference. The means score of the learners pre-test in exactness is 65.31, whereas the post-test was high than 83.12. It implies that there is significance diverse. The results of advancement speaking from pre-test to post-test talking fluency is 26.29% and speaking accuracy is 27.26%. Therefore, Brainstorming Technique gives effect on students’ speaking skill.